"Or so the government would have you believe": Uses of "you" in Guardian editorials. (December 2015) - Breeze, Ruth
Abstract: Although second person pronouns are relatively unusual in formal written genres, they are frequent in the editorials of some newspapers. This has been associated with ongoing trends towards a more informal style of public discourse, and with the construction of more equal relationships between writers and readers, which may be either ideologically or economically motivated. This analysis of all the instances of "you" in Guardian editorials for 2011 brings to light several different ways in which the writer employs the second person. Although the primary motivation appears to be epideictic, in that the writer seeks to forge strong bonds with the readership and thereby strengthen the sense of communion and shared values, some other uses are identified, including dramatisation and irony. This leads on to consideration of the type of reader constructed by these uses of "you", and the relationships projected between writer/newspaper, reader, and other entities. Highlights: Second-person pronouns are frequent in Guardian editorials. The uses of "you" can be divided into dialogic and non-dialogic uses. Use of "you" constructs various types of relationship with readers. This points to wider trends towards informalisation and discursive democratisation.